Efficacy of Ozoralizumab vs. Golimumab for Rheumatoid Arthritis: A Systematic Review - Fithriyah, Nathania Elma; Rahmadhani, Khafiyah Hikmah; Susanti, Luthfiana Rofhani; Mustika, Arifa; Lita Diah Rahmawati; Wungu, Citrawati Dyah Kencono (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Rheumatoid arthritis, a systemic autoimmune disease, affects 13% of the world population. As a well-established therapy, golimumab provides a key benchmark for assessing novel biological treatments. In contrast, ozoralizumab represents an innovative therapeutic approach. This study aimed to comprehensively elucidate the efficacy of golimumab and ozoralizumab in reducing rheumatoid arthritis disease activity. Methods: Literature searches were conducted throughout PubMed, Cochrane, and Web of Science using Boolean operators, covering available records from database inception until October 2024. The literature search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The included studies were randomized controlled trials (RCT) evaluating the efficacy of ozoralizumab or golimumab for rheumatoid arthritis. Five studies from 2015 to 2022 were obtained and assessed using the Cochrane Risk of Bias 2 (ROB2) tool. Results: The five studies consisted of two ozoralizumab trials and three golimumab trials conducted in Japan and the United States, involving 2,305 participants. All included studies exhibited a low risk of bias based on assessments undertaken using the ROB2 tool. The differences in Disease Activity Score-28 (DAS28) remission rates between ozoralizumab and placebo were 42.6% in one study and 6.3% in the other, whereas golimumab mainly showed smaller differences versus placebo across three studies (4.6%, 5.9%, and 10.4%). Conclusion: This study demonstrates DAS28 remission in rheumatoid arthritis patients receiving either ozoralizumab or golimumab therapy. Nonetheless, further direct statistical studies are essential to determine which therapy is superior and under what circumstances it should be administered.   Highlights: 1. This study provides robust evidence that establishes ozoralizumab as a novel tumor necrosis factor-alpha (TNF-α) inhibitor for rheumatoid arthritis. 2. According to the findings, ozoralizumab may be a clinician's choice due to its comparable efficacy and potential advantages over golimumab.